ANALISIS PROPORSI BELANJA MODAL TERHADAP TOTAL BELANJA DAERAH KABUPATEN BUNGO - Nur'aini Nur'aini (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
The title of this thesis is Analysis of the Proportion of Capital Expenditure to Total Regional Expenditure of Bungo Regency. Advisor Dra. Rahma Nurjanah, M.Sc. The purpose of this research is to know and analyze the development of capital expenditure and regional spending in Bungo in 2006-2012, to know and analyze the proportion of capital expenditure in Bungo Regency in 2006-2012. The analytical method used is a quantitative descriptive method. The results showed that the development of capital spending in Bungo Regency during 2006-2012 was an average of 12.00% per year and the average development of regional spending during 2006-2012 was 13.11% per year. Then the proportion of capital expenditure to total regional expenditure in Bungo Regency in 2006-2012 averaged 26.60% per year.